Meaning-Making of Motherhood Among Mothers With Substance Abuse Problems - To, Siu-ming; Yan, Ming-wai; Lau, Cheryl Danielle (Frontiers in Psychology, 2021)
Previous literature has documented the unique challenges encountered by mothers with substance abuse problems, which may hinder the ability to fulfill parenting responsibilities. Since there is evidence suggesting the engagement in meaning-making processes can help individuals reinterpret their transitions into parenthood and in coping with parental stress, this study examined the meaning-making processes of motherhood among mothers with substance abuse problems. Sixteen Hong Kong Chinese mothers with a history of substance abuse were purposively selected and invited to narrate their life and maternal experiences in individual interviews. Based on the meaning-making model in the context of stress and coping, whereby global meaning refers to one’s orienting system and situational meaning refers to the meaning one attributes to a particular situation, the participants’ global and situational meanings related to motherhood and substance use, and their reappraised meanings in response to the discrepancies between global and situational meanings were analyzed. Using thematic analysis, the results showed when faced with an internal conflict between one’s global and situational meanings induced by substance abuse, most participants engaged in the meaning-making process of assimilation. Rather than changing their inherent parental beliefs and values, most participants adjusted their appraisals toward the situation and hence made changes in their cognitions or behaviors such as making efforts to quit substance use or reprioritizing their parenting responsibilities. The analysis further revealed being a mother provided a significant source of meaning to the participants in confronting highly stressful mothering experiences induced by substance abuse. Altogether, the findings suggest that a meaning-making approach may have benefits and implications for helping this population reorganize their self-perceptions, gain a clearer sense of future direction in motherhood, and achieve more positive life and parenting outcomes.